2006
DOI: 10.1373/clinchem.2006.074971
|View full text |Cite
|
Sign up to set email alerts
|

Use of Routinely Collected Amniotic Fluid for Whole-Genome Expression Analysis of Polygenic Disorders

Abstract: Background: Neural tube defects related to polygenic disorders are the second most common birth defects in the world, but no molecular biologic tests are available to analyze the genes involved in the pathomechanism of these disorders. We explored the use of routinely collected amniotic fluid to characterize the differential gene expression profiles of polygenic disorders. Methods: We used oligonucleotide microarrays to analyze amniotic fluid samples obtained from pregnant women carrying fetuses with neural tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…For example, gene expression studies may accelerate our understanding of mechanism. 32 The role of leptin in placental and fetal growth and the potential utility of AFL in pregnancy management are promising and require further study. In summary, these results are important in assessing the impact of AFL levels to maternal and fetal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gene expression studies may accelerate our understanding of mechanism. 32 The role of leptin in placental and fetal growth and the potential utility of AFL in pregnancy management are promising and require further study. In summary, these results are important in assessing the impact of AFL levels to maternal and fetal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also shown that high LST1 expression levels are associated with several inflammatory diseases including rheumatoid arthritis (4) and the inflammatory response believed to cause neural tube defect. (8) These associations, however, have been established based on mRNA expression data and have not been validated at the protein level. To allow insights into the structure and function of LST1 isoforms and to discern their potential role in autoimmune diseases, we generated and characterized rat monoclonal antibodies specific for LST1.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have recently found transmembrane LST1 to regulate cell-cell communication [12]. Several studies have proposed that LST1 may play a role in inflammatory diseases including Reactive Arthritis [13], Lupus Nephritis [14] and the inflammatory response believed to cause Neural Tube Defect [15]. These studies correlated high levels of LST1 expression with inflammatory pathologies, thereby further substantiating a potential link between LST1 protein levels and inflammation.…”
Section: Introductionmentioning
confidence: 60%